Strengthening Midwives’ Role in Reproductive and Mental Health Counselling for Adolescent Girls: A Narrative Review - Karunia Wijayanti; Resinta Mareta Putri; Sofia Al Farizi (Journal of Research in Midwifery and Healthcare, 2026)
Background: Adolescence is a pivotal window for lifelong health, yet adolescent girls face persistent sexual and reproductive health (SRH) and mental health (MH) burdens amid stigma, access barriers, and digital-era risks, necessitating midwife-led responses. Purpose: This study aims to examine how the role of midwives with various interventions can optimise the reproductive and mental health of adolescent girls. Methods: Narrative review of studies published in the last five years. A computerised search identified 1.032 records (PubMed=666; ScienceDirect=325; Scopus=41). Titles/abstracts were screened using prespecified inclusion criteria (English; alignment with the objective). Fifteen studies involving girls aged 10–19 years in clinics, schools, communities, and primary-care settings were included. Data on midwife-led SRH–MH interventions were extracted and synthesised thematically. Results: Midwife-delivered, youth-friendly SRH–MH models were feasible and acceptable, and were associated with increased SRH service uptake, better engagement and continuity, and reductions in depressive/anxiety symptoms in several digital or hybrid interventions. Enablers included confidentiality, respectful non-judgmental counselling, trained staff, clear referral pathways, and flexible access; barriers included stigma, privacy concerns, costs/transport, and restrictive social norms. Conclusion: Midwife-led, integrated, and digitally enabled SRH–MH services show promise for optimising outcomes among adolescent girls. Implications for midwifery practice include adopting AYFHS standards, institutionalising routine PHQ-A/GAD-7 screening with referral pathways, ensuring confidential, trauma-informed counselling and contraceptive choice, leveraging blended in-person/mobile follow-up, and monitoring quality indicators (screening coverage, service use, completed referrals).